Pediatric Cystine Calculi in West of Iran: A Study of 22 Cases - Seyedzadeh, Abolhassan; Momtaz, Hossein; Moradi, Mahmoud Reza; Moradi, Asad (Urology Journal, 2009)
Introduction: Cystinuria is an autosomal recessive disorder which clinically presents as cystine calculi. In this study, we reviewed cystine calculi cases in the west of Iran to determine their common presentations and response to different therapeutic modalities. Materials and Methods: Between 1999 and 2005, we had 22 pediatric patients (11 boys and 11 girls) with cystine calculi. The demographic characteristics and clinical data of the patients as well as the treatment results were reviewed. Results: The mean age of the patients was 34.20 ± 42.99 months (range, 4 to 156 months). They were followed for a mean duration of 23 months (range, 3 to 70 months). Thirteen patients (59.1%) had bilateral and 9 (41%) had unilateral kidney calculi. The sizes of the calculi were between 2 mm and 20 mm. Nine patients (41%) had renal atrophic changes and 1 (4.5%) had obstructive acute renal failure. Hydration and urinary alkalinization were administrated to all of the patients which yielded an excellent result in 54.5% and a poor response in 27.2%. Captopril started for 5 patients was effective only in 1. D-penicillamine had no favorable response. Extracorporeal shockwave lithotripsy was successful in 5 attempts and failed in 4. Surgical interventions were performed for 13 patients (59.1%) and 6 (27.2%) required more than 1 surgical operation. Conclusion: We recommend metabolic workup of childhood urolithiasis and appropriate medical management of its underlying disease. We also recommend minimally invasive urologic techniques including shockwave lithotripsy only when there are clear indications for nonmedical procedures.